2019
DOI: 10.1016/j.ijrobp.2019.03.015
|View full text |Cite
|
Sign up to set email alerts
|

MRE11 as a Predictive Biomarker of Outcome After Radiation Therapy in Bladder Cancer

Abstract: Purpose Organ-confined muscle-invasive bladder cancer is treated with cystectomy or bladder preservation techniques, including radiation therapy. There are currently no biomarkers to inform management decisions and aid patient choice. Previously we showed high levels of MRE11 protein, assessed by immunohistochemistry (IHC), predicted outcome after radiation therapy, but not cystectomy. Therefore, we sought to develop the MRE11 IHC assay for clinical use and define its relationship to clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…It has been reported that high levels of MRE11 predict the outcome after radical radiotherapy [132, 133]. However, Walker et al later showed that there is no significant association between MRE11 and the rate of success of radiation-based bladder preservation therapy [134]. This inconsistency may be attributed to the lack of an automated quantitative methods or standard reassessment of MRE11.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that high levels of MRE11 predict the outcome after radical radiotherapy [132, 133]. However, Walker et al later showed that there is no significant association between MRE11 and the rate of success of radiation-based bladder preservation therapy [134]. This inconsistency may be attributed to the lack of an automated quantitative methods or standard reassessment of MRE11.…”
Section: Introductionmentioning
confidence: 99%
“…Pre‐treatment bladder cancer expression of DSB repair gene MRE11 was found to be predictive of survival following radical radiotherapy but not cystectomy by the Kiltie group, a result that was independently verified by Laurberg et al Interestingly, the SNP rs1805363 in MRE11A was also found predictive of survival in a gene‐dosage effect in patients with bladder cancer treated by radical radiotherapy but not by cystectomy . New work by the Kiltie group aimed to standardize and develop a clinical assay for MRE11 immunohistochemistry assay across several centers in the United Kingdom using transurethral resection of bladder (TURBT) samples from prior bladder‐preservation trials . However, they were unable to replicate prior results, which was attributed to problems in automatic staining and poor scoring reproducibility among histopathologists.…”
Section: Tumor Radiosensitivitymentioning
confidence: 93%
“…74 New work by the Kiltie group aimed to standardize and develop a clinical assay for MRE11 immunohistochemistry assay across several centers in the United Kingdom using transurethral resection of bladder (TURBT) samples from prior bladder-preservation trials. 75 However, they were unable to replicate prior results, which was attributed to problems in automatic staining and poor scoring reproducibility among histopathologists.…”
Section: A Gene Expression To Predict Radiotherapy Benefitmentioning
confidence: 98%
“…Unfortunately, even the most promising biomarkers, such as double strand break repair nuclease MRE11 (MRE11), have failed to generate reproducible data. In the latest multicentre collaborative effort to validate MRE11 as a biomarker, the immunohistochemistry scoring results varied considerably and failed to attain a reliable dataset [ 33 ]. Finally, a complete or near complete response assessed by cystoscopy after 4–5 weeks induction phase remains as the only reliable predictor of treatment outcome [ 34 , 35 ]…”
Section: Limitations Of Use Of Rt In Mibc In Clinicsmentioning
confidence: 99%